Pregnant adolescent self-care in the prevention of risk factors of Hypertensive Disorders in Pregnancy (HDP) - doi:10.5020/18061230.2007.p173 - Zélia Maria de Sousa Araújo Santos; Mariza Galassi Neves; Jennara Cândido do Nascimento; Helexciana Teixeira Fernandes; Janaina da Silva Feitoza (Universidade de Fortaleza, 2012)
Adolescent pregnancy is considered a problem for public health, due to the high mortality related to hypertensive disorders in pregnancy - HDP. This was a descriptive study with the aim of analyzing the pregnant adolescent self-care in the prevention of HDP risk factors. It was carried out in the Nucleus of Integrated Medical Attention - NAMI, in Fortaleza - Ceará, with twenty women from the Dendê Community, taken care of in the prenatal ambulatory of that institution, during the months of September and October, 2005. The data were collected by means of interview. The pregnant adolescents informed precarious socio-economic conditions, low schooling and other risk factors for HDP, beyond the age: black color, familiar history, arterial hypertension (AH), diabetes mellitus, renal illness and emotional conflicts. The knowledge on the prevention of risk factors was restricted to five (25%) pregnant adolescents; however it was reduced to fragmented information, and the preventive behaviors related to feeding habit, smoke and alcoholism cessation, and physical exercise. Therefore, it was evidenced among the adolescents the unsatisfactory exercise of self-care activities, aiming at preventing HDP risk factors; that beyond the age, they presented other predisposing factors to this disorders; that they were susceptible to preventive behaviors and/or control, as in the case of chronic-degenerative illnesses - AH and diabetes mellitus. Probably, this behavior was associated to the elementary and fragmented knowledge, and the absence or the deficiency of family participation in health promotion actions, mainly in those inherent to the prenatal follow-up.